The Differences in Knowledge of Balanced Nutrition Between Obese and Non-Obese Women in Rural Area - Hildagardis Meliyani Erista Nai; Maria Amrijati Lubijarsih (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Obesity including central obesity is a risk factor for several diseases such as cardiovascular disease, type II diabetes, musculoskeletal disorders, and cancer. The underlying cause of obesity and overweight is an energy imbalance between calories consumed and calories expended. Nutritional knowledge is important in determining the food consumed. Balanced Nutrition Guidelines are intended to provide guidance on conceptual daily consumption and healthy living behaviors based on the principles of consumption of various foods, clean living behavior, physical activity, and regular weight control in order to maintain a normal body weight. The objective of this study was to analyze the differences in knowledge of balanced nutrition between obese and non-obese adult women. This type of this research was an observational study with a cross-sectional design. The subjects of this study were adult women aged 20-49 years, amounts 120 people. The sample was taken by simple random sampling. Analysis results showed that there were no significant differences in age, education level, employment status, marital status, number of family members, and physical activity between adult women who were central obese and who were not central obese (p>0.05). There was no significant difference in balanced nutrition knowledge between adult women who were central obese and who were not central obese (p=0.77). The balanced nutrition knowledge of adult women is still in the medium and low category. It is suggested to do more intense socialization regarding Balanced Nutrition Guidelines to the public using easily understood media.